Gender Gap in the Leadership of Health Institutions: The Influence of Hospital-Level Factors (Mary Ann Liebert, 2021)
Objective: To analyze whether the increased representation of women in the health field is accompanied by a greater presence in leadership positions in the public health system and whether there are differences according to the hospital level. Methods: A descriptive study of the distribution of leadership positions by sex and type of hospital within the health centers of a regional public health system. Results: In total, 74.01% of the professionals were women. The representation of women in management positions was 33.1%, and among service chiefs, it was 24.01%. In the service headings, we observed that surgical specialties had a lower representation of women (30.9% in medical specialties vs. 18.1% in surgical specialties, p<0.0001). By type of hospital, no differences were found in the management positions, but there were differences in the medical chiefs, with less female representation in the regional hospitals (28.6% vs. 39.7%, p=0.003). Conclusion: Women represent the majority in the public health system. Nonetheless, their representation in positions of greater responsibility and decision-making is very limited, being particularly low in county hospitals. Increasing female representation in these positions is a current challenge for society, and equality policies need to be developed and applied to minimize this gender gap.